Suspending Syntax: Bodily Strain and Progressivity in Talk - Hofstetter, Emily; Keevallik, Leelo; Löfgren, Agnes (Frontiers in Communication, 2021)
People speak not only under relaxed conditions but also during strenuous activities, and grammatical resources can be used to achieve displays of strain. This study looks at the relationship between progressivity of talk and bodily strain, focusing on the practice of temporarily suspending syntax while the speaker is accomplishing a physically challenging task. Based on examples from two different physical activities, rock climbing and opera rehearsals, the paper argues that the practice of suspending syntax is a resource available across contexts to render prominence to the strained body and highlight ongoing movement or other bodily action. By placing the strain-based display of incapacity at a moment when the emerging syntactic structure is incomplete, participants maintain rights to resume talk while also presenting themselves as possessing the physical capacity to do so. Suspending syntax is shown to be a minutely timed speakers’ technique that takes advantage of the emergent nature of syntax and that demonstrates how speakers organize language in relation to the sensing and moving body.